Similar slow down in running speed progression in species under human pressure - Desgorces, F. D.; Berthelot, G.; Charmantier, A.; Tafflet, M.; Schaal, K.; Jarne, P.; Toussaint, J.-F. (Journal of Evolutionary Biology, 2012)
Running speed in animals depends on both genetic and environmental conditions. Maximal speeds were here analysed in horses, dogs and humans using data sets on the 10 best performers covering more than a century of races. This includes a variety of distances in humans (200-1500 m). Speed has been progressing fast in the three species, and this has been followed by a plateau. Based on a Gompertz model, the current best performances reach 97.4% of maximal velocity in greyhounds to 100.3 in humans. Further analysis based on a subset of individuals and using an `animal model` shows that running speed is heritable in horses (h2 = 0.438, P = 0.01) and almost so in dogs (h2 = 0.183, P = 0.08), suggesting the involvement of genetic factors. Speed progression in humans is more likely due to an enlarged population of runners, associated with improved training practices. The analysis of a data subset (40 last years in 800 and 1500 m) further showed that East Africans have strikingly improved their speed, now reaching the upper part of the human distribution, whereas that of Nordic runners stagnated in the 800 m and even declined in the 1500 m. Although speed progression in dogs and horses on one side and humans on the other has not been affected by the same genetic/environmental balance of forces, it is likely that further progress will be extremely limited.